A liver-on-a-chip platform with bioprinted hepatic spheroids. (12th January 2016) - Bhise, Nupura S; Manoharan, Vijayan; Massa, Solange; Tamayol, Ali; Ghaderi, Masoumeh; Miscuglio, Mario; Lang, Qi; Shrike Zhang, Yu; Shin, Su Ryon; Calzone, Giovanni; Annabi, Nasim; Shupe, Thomas D; et al.
Abstract: The inadequacy of animal models in correctly predicting drug and biothreat agent toxicity in humans has resulted in a pressing need for in vitro models that can recreate the in vivo scenario. One of the most important organs in the assessment of drug toxicity is liver. Here, we report the development of a liver-on-a-chip platform for long-term culture of three-dimensional (3D) human HepG2/C3A spheroids for drug toxicity assessment. The bioreactor design allowed for in situ monitoring of the culture environment by enabling direct access to the hepatic construct during the experiment without compromising the platform operation. The engineered bioreactor could be interfaced with a bioprinter to fabricate 3D hepatic constructs of spheroids encapsulated within photocrosslinkable gelatin methacryloyl (GelMA) hydrogel. The engineered hepatic construct remained functional during the 30 days culture period as assessed by monitoring the secretion rates of albumin, alpha-1 antitrypsin, transferrin, and ceruloplasmin, as well as immunostaining for the hepatocyte markers, cytokeratin 18, MRP2 bile canalicular protein and tight junction protein ZO-1. Treatment with 15 mM acetaminophen induced a toxic response in the hepatic construct that was similar to published studies on animal and other in vitro models, thus providing a proof-of-concept demonstration of the utility of this liver-on-a-chip platform for toxicity assessment.